Análisis del personaje audiovisual Pablo Escobar de la serie Escobar: el patrón del mal desde la narrativa fílmica. - Poma Guarnizo, Viviana Salome (2024)
This paper focuses on the analysis of the audiovisual character of Pablo Escobar in the series "Escobar: El patrón del mal" from the perspective of filmic narrative. The main objective of the work is to unravel the complexities of the character and his representation in the series. To achieve this, a qualitative methodology was implemented that included the observation technique and the use of categorized observation cards, which were built from the methodology of analysis of the film character: a narrative proposal developed by Pérez (2016). Through this approach, the actions, motivations and development of the character throughout the narrative were examined in detail. The main results revealed a deep and multifaceted characterization of Pablo Escobar, showing how the series uses diverse narrative and visual resources to build a complex portrait of the Colombian drug trafficker. In addition, key elements were identified that contribute to the understanding of the character's psychology and his role in the development of the plot. This analysis provides an enriching insight into the filmic narrative and understanding of controversial and multifaceted characters on screen Keywords: abstract, phenomenological, formal, narco - series, Pablo Escobar.